LATITUDINAL DISTRIBUTION OF CARBON-MONOXIDE IN THE DEEP ATMOSPHERE OF VENUS - Collard, A; Taylor, F; Calcutt, S; Carlson, R; Kamp, L; Baines, K; Encrenaz, T; Drossart, P; Lellouch, E; Bezard, B (1993)
A large number of i.r. spectra of Venus was obtained using the Near-Infrared Mapping Spectrometer (NIMS) on the Galileo spacecraft, during the February 1990 encounter. Preliminary results show an apparent increase in the tropospheric CO volume mixing ratio (vmr) in the northern polar region. Other possible explanations of the observations are examined and rejected and an increase of the CO abundance north of 47°N of (35 ± 15)% is inferred. Some possible causes of this enhancement are suggested. © 1993.